2017
DOI: 10.1136/bmjopen-2016-013632
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a scoping review study to identify and classify patient-centred quality indicators

Abstract: IntroductionThe concept of patient-centred care (PCC) is changing the way healthcare is understood, accepted and delivered. The Institute of Medicine has defined PCC as 1 of its 6 aims to improve healthcare quality. However, in Canada, there are currently no nationwide standards in place for measuring and evaluating healthcare from a patient-centred approach. In this paper, we outline our scoping review protocol to systematically review published and unpublished literature specific to patient-centred quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 14 publications
0
25
0
2
Order By: Relevance
“…A number of sources included in the review were identified through a scoping review conducted on person‐centred quality indicators that revealed rich literature on PCC practice and measurement. Search protocol details, including databases and search terms, have been published . Additional works that were hand‐searched and selected included frequently cited PCC literature and key policy documents from reference lists, and those identified by our patient partner (Zelinsky).…”
Section: Methodsmentioning
confidence: 99%
“…A number of sources included in the review were identified through a scoping review conducted on person‐centred quality indicators that revealed rich literature on PCC practice and measurement. Search protocol details, including databases and search terms, have been published . Additional works that were hand‐searched and selected included frequently cited PCC literature and key policy documents from reference lists, and those identified by our patient partner (Zelinsky).…”
Section: Methodsmentioning
confidence: 99%
“…In our search, we found no consensus on a definition, and we developed an operational definition for the purpose of this environmental scan. 21 We defined patient-centred quality indicators as the unit of measurement of health care system or organizational or individual performance that quantify patients' and families' experiences with the care received and quantify the experience of any individual who needs to have contact with health care services. To reduce response bias, examples were not provided in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review of the peer-reviewed and grey literature was conducted previously and published elsewhere. 21 In addition to this, we performed a Google search between July 2016 and September 2016 to understand how various health care jurisdictions in Canada, England, Sweden, New Zealand and Australia were measuring patient-centred care and whether patient-centred quality indicators were used. We searched the websites of health care organizations and jurisdictions from the 5 countries using keywords such as "patient (or person)-centred care," "patient (or person)-centred care/patient experience measurement," "patient (or person)-centred care/patient experience measures," "quality indicators" and "quality improvement" to identify potential participants to contact regarding measurement of patient-centred care.…”
Section: Settingmentioning
confidence: 99%
“…A escolha dos estudos não está focada na qualidade da investigação (pois essa avaliação não faz parte, do objetivo da scoping review), envolve ou não recolha de dados, apresenta uma síntese essencialmente qualitativa e raramente quantitativa 6 Na etapa 3, seleção dos estudos o processo de revisão consistiu em dois níveis. No primeiro nível, uma revisão através dos títulos e resumos, e no segundo nível, uma revisão do texto total 10 . Nesta, os critérios de inclusão foram: artigos originais de investigação e dissertações de mestrado e doutoramento sobre a realidade portuguesa, ou que abordem os conceitos básicos da questão de investigação (intervenção / intervenções / responsabilidades do enfermeiro e saúde / saúde pública, ou seus similares, competências / papel do enfermeiro, exercício profissional, saúde comunitária), prioritariamente referentes a Portugal, escritos em português, espanhol e inglês.…”
Section: Métodounclassified